Analisis Komperatif Terkait Bunga Dan Dampak Akan Kesenjangan Umat Pada Bank Konvensional Dan Bank Syariah - Delvi Salwa Nakita; Enika Diana Batubara; Hilman Fauzi Lubis; Julaikha Nasution (Jurnal Ilmiah Wahana Pendidikan, 2023)
This writing examines a problem in society, especially Muslims, about the importance of sorting and being careful in making good in accordance with the teachings of Shari’ah. Because this can trigger a servant to slip in sin and no doubt will go to hell. Therefore, the importance of transactions that are in accordance with Islamic teachings must be practiced by Muslims today to avoid things that smell harmful or even unlawful as early as possible. One of the forms of haram is the abuse of transactions in the form of usury. Islam strictly prohibits this practice as Allah mentions in Q.S Al-Baqarah verse 275. The prohibition of usury has various forms of application. Among them transactions in a bank institution. It is not surprising that banking is one of the transaction practices that raises more or less harm to humans, although there is also a positive side that can be enjoyed by society in general, especially Muslims, with various variations of opinion from one another. This approach uses normative sociological methods, by describing events that occur in the community and the information taken from this study comes from perceptions and interviews with several informants as an exploratory test. In addition, the authors utilize other additional sources, in the form of books, journals, and other scientific papers to support basic information.